Campylobacter fetus subsp. fetus ovine abortion outbreak in Argentina - Fiorentino, Maria Andrea (2017)
Campylobacter infection is one of the major causes of ovine abortionsworldwide. However there are no previous reports of Campylobacter fetussubspecies fetus associated to outbreak ovine abortion in Argentina. Thisstudy constitutes the first report of C. fetus fetus outbreak ovine abortion innaturally infected ewes in Argentina. The problem was presented in a dairyflock of 205 pampinta ewes. In one week 7 abortions were recorded. Some ofthe aborted sheep also retained placentas and showed vaginal discharges.Twins and three placentas were sampled to determine the cause of theabortions. C. fetus fetus was isolated in lung, liver and abomasal fluids fromboth fetuses and in 2 out of 3 placentas. C. fetus fetus DNA was detected in2/3 placentas tested and in lungs of both fetuses. Additionally, N. caninumDNA was amplified in a ewe placenta. No N. caninum or T. gondii serologicaltests were carried out in the ewes, therefore these protozoa infection couldnot be ruled out in the flock. Toxoplasma and Neospora infection are relativelycommon in Argentinean flocks. However, protozoan abortion in smallruminants has not been extensively reported, therefore it is important to ruleout the presence of these pathogens when ovine abortions are registered.Further work is needed in order to quantify the impact of C. fetus fetusinfection in sheep production systems of the region.